Prevalence and antimicrobial resistance of extended spectrum beta-lactamase (ESBL) producing Klebsiella spp. in poultry meat - Fatema Yeasmin Tanni; Md. Shahidur Rahman Chowdhury; Hemayet Hossain; Md. Atik Faysal; Md. Anisur Rahman; Ahsan Al Emon; Mashuka Nahida Asha; Md. Mukter Hossain; Md. Mahfujur Rahman (Heliyon)
Klebsiella spp. present in the food chain have been of much interest during the last few decades due to their implication in the development of antimicrobial resistance. We determined the prevalence of Klebsiella spp. (Klebsiella pneumoniae and Klebsiella oxytoca) in retail poultry meat, along with their resistance profile against antimicrobials. For the detection of the Klebsiella spp. a total of 285 raw meat samples of retailed poultry were collected and cultured. All positive cultures were screened for Klebsiella spp. by PCR to confirm the identity. Their antimicrobial susceptibility pattern was performed using the disk diffusion technique, whereas the ESBL-coding genes were detected using the multiplex PCR technique. Out of 285 samples, 139 (48.77 %) raw meat samples had Klebsiella spp. While out of 139 identified positive isolates, 99 (34.74 %) isolates were K. pneumoniae, and 13 (4.56 %) were K. oxytoca. Phenotypically, most of the strains were fully (100 %) resistant to ampicillin, amoxicillin, cefuroxime, ceftazidime, and nalidixic acid. Of the β-Lactamase genes that were detected through mPCR, blaSHV was the dominant gene among the strains K. pneumoniae and K. oxytoca isolates, with percentages of 86.87 % and 76.92 %, respectively. Besides, isolates of K. pneumoniae harbored 95.96 % (95 % CI: 89.98–98.89) of the tetA gene, whereas the K. oxytoca isolates harbored only 92.31 % (95 % CI: 63.97–99.81) of the tetA gene. Most of the K. pneumoniae and K. oxytoca isolates were found to harbor the streptomycin-resistant gene, strA. These results highlighted significant carriage of multidrug-resistant (MDR) Klebsiella spp. in retail poultry meat, which insinuates that there is a need for a strategic plan in place to curb the dissemination of these multi drug resistant pathogens along the food chain.